Effects of shoreline alteration and habitat heterogeneity on macroinvertebrate community composition across European lakes. (March 2019) - Porst, Gwendolin; Brauns, Mario; Irvine, Kenneth; Solimini, Angelo; Sandin, Leonard; Pusch, Martin; Miler, Oliver
Highlights: The effect of morphological alterations to lake littoral zones was investigated. Macroinvertebrate communities differed among shore types and habitats. Morphological alteration had a negative effect on macroinvertebrate biodiversity. Regional indicator taxa were identified for different shore types and habitats. We validated the use of macroinvertebrates to assess morphological alterations. Abstract: Human lake shore alterations often result in a substantial decrease of littoral and riparian habitat diversity and physical complexity, but the intensity at which shore alterations affect biodiversity may differ among European geographical regions. We tested if the response of littoral macroinvertebrate communities to human shoreline alterations is consistent among geographical regions. We compared community composition and diversity of human altered with those of unmodified littoral zones from 51 lakes across seven European countries in four geographical regions based on pooled composite as well as habitat-specific macroinvertebrate samples. Taxon richness and community composition differed among shore types and different habitats in all geographic regions, with morphological alteration having an overall negative effect on macroinvertebrate taxon richness. In addition, habitat heterogeneity also had a strong effect on littoral communities, with highest taxon richness found in the structurally complex macrophyte habitats in all regions. Average proportional densities of Diptera and Oligochaeta taxa generally increased in morphologically altered shores in all geographical regions, while Bivalvia, Crustacea, Ephemeroptera, Gastropoda and Trichoptera showed comparatively lower numbers in many anthropogenically altered sites. Furthermore, taxon richness was positively correlated with habitat diversity. We were able to relate changes in littoral communities to anthropogenic shoreline alterations, and linked the effect to the loss of habitats and habitat complexity. The results of our study demonstrate that littoral macroinvertebrates respond consistently negative to the influence of morphological alterations across European geographical regions in terms of biodiversity. While macroinvertebrates have previously been identified to be useful descriptors of morphological change in single countries/regions, we can now validate that they can be used to assess the ecological status of lakes in terms of morphological alterations across European regions. Our results can be used to further improve ealready existing WFD-compliant multimetric indices, for example by including taxa groups, which show a strong reaction to shoreline alterations. This could be supported by the inclusion of a suit of indicator taxa reflecting the loss of complex habitats such as macrophytes in the lake littoral.